Speed impacts frontal-plane maneuver stability of individuals with incomplete spinal cord injury. (January 2020) - Viramontes, Carolina; Wu, Mengnan/Mary; Acasio, Julian; Kim, Janis; Gordon, Keith E.
Abstract: Background: Following incomplete spinal cord injury, people often move slowly in an effort to maintain stability during walking maneuvers. Here we examine how maneuver speed impacts frontal-plane stability in people with incomplete spinal cord injury. We hypothesized that the challenge to control frontal-plane stability would increase with maneuver speed; specifically, the minimum lateral margin of stability would be smaller and the required coefficient of friction to avoid a slip would be greater during fast vs. preferred speed maneuvers. Methods: We measured kinematics and ground reaction forces as 12 individuals with incomplete spinal cord injury performed side-step, lateral maneuvers at preferred and fast speeds. We examined four sequential steps: the Setup and Pushoff steps initiated the maneuver, and the Landing and Recovery steps arrested the maneuver. Findings: Our hypotheses were partially supported. Maneuver time was shorter during fast vs. preferred speed maneuvers (p = 0.003). Minimum lateral margin of stability was smaller during the Setup step of fast vs. preferred speed maneuvers (p = 0.026). We found no differences in minimum lateral margin of stability between speeds for the Landing and Recovery steps (p > 0.05). The required coefficient of friction was not different between fast and preferred speed maneuvers (p = 0.087). Interpretation: The greatest effect of increasing maneuver speed occurred during the Setup step; as speed increased, participants reduced their minimum lateral margin of stability ipsilateral to the maneuver direction. This action allowed maneuvers to be performed more quickly without requiring a greater lateral impulse during the Pushoff step. However, this strategy reduced passive stability. Highlights: People with incomplete spinal cord injury can increase walking maneuver speed. People reduced their margin of stability as lateral maneuver speed increased. Reducing the lateral margin of stability will enable faster maneuvers.